2022
DOI: 10.3389/fvets.2022.875657
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course and Diagnostic Findings of Biopsy Controlled Presumed Immune-Mediated Polyneuropathy in 70 European Cats

Abstract: There is a paucity of information on the clinical course and outcome of young cats with polyneuropathy. The aim of the study was to describe the clinical features, diagnostic investigations, and outcome of a large cohort of cats with inflammatory polyneuropathy from several European countries. Seventy cats with inflammatory infiltrates in intramuscular nerves and/or peripheral nerve biopsies were retrospectively included. Information from medical records and follow up were acquired via questionnaires filled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(41 citation statements)
references
References 64 publications
(110 reference statements)
5
35
1
Order By: Relevance
“…These changes are consistent with previous reports in the literature and support the presence both of demyelination and axonal loss in IPN-cats. 5,6,16 Conversely, histological examinations conducted on peripheral nerve biopsies taken from IPN-cats show evidence of demyelination and remyelination, less commonly axonal degeneration and regeneration, and variable inflammatory infiltrates. Muscle biopsies from affected cats commonly show a loss of myelinated intramuscular nerve fibres with or without mononuclear infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are consistent with previous reports in the literature and support the presence both of demyelination and axonal loss in IPN-cats. 5,6,16 Conversely, histological examinations conducted on peripheral nerve biopsies taken from IPN-cats show evidence of demyelination and remyelination, less commonly axonal degeneration and regeneration, and variable inflammatory infiltrates. Muscle biopsies from affected cats commonly show a loss of myelinated intramuscular nerve fibres with or without mononuclear infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…Cranial nerve involvement in cats with (suspected) polyneuropathies is not common. 19,20 In a recent study published of cats with immune-mediated polyneuropathy, 17% of the study population showed signs of cranial nerve involvement. 20 EMG of the limb muscles showed abnormalities consistent with denervation.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In a recent study published of cats with immune-mediated polyneuropathy, 17% of the study population showed signs of cranial nerve involvement. 20 EMG of the limb muscles showed abnormalities consistent with denervation. However, EMG abnormalities could not be observed in the masseter and temporalis muscles, which we had expected to be present due to the trigeminal nerve motor deficits (weak masticatory muscle tone).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery was defined as the state in which the cat could walk without assistance and could jump onto objects. Results of patient history, onset of clinical signs, course of the disease, neurological examination, results of the electrophysiological examination, imaging findings including MRI and CT, laboratory workup, and outcome are described by van Renen et al (28).…”
Section: Online Questionnairementioning
confidence: 99%